PENGEMBANGAN BAHAN AJAR BERBASIS AKTIVITAS DENGAN MEDIA CD INTERAKTIF PADA MATERI INDERA PENDENGARAN DAN SISTEM SONAR - Nurmariza, Arni; Ibrahim, Muslimin; Widodo, Wahono (Universitas Negeri Surabaya, 2016)
This research aims to develop the activities-based instructional material in junior high school natural science learning on sense of hearing and sonar systems topic through Media Interactive CD to improve learning achievement. This research use research and development. The model used is taken from Dick and Carey?s developmental model. The tests used are one group pre-test and post-test. The data analysis technique used descriptive quantitative and qualitative. The results showed that (1) the validation of teaching materials id categorized as feasible, (2) the feasibility of teaching materials with the average score of 3.7 is categorized as good, the percentages of students' response to learning and media are 98.81% and 90.48% , categorized as very good, 99,29% legibility of media is categorized as very good, (3) the effective teaching materials to reach the achievement of students? competency and activate students gets an average score of 3.25, the cognitive aspect of learning outcomes is categorized as